Strategic Advertising Campaigns / Second Edition - Brown P. William; Martin Dennis; Schultz Don E; Ntc Business Books (1987)
Preface, Introduction: What Advertising Is All About, Marketing and the Marketing Plan and Advertising, Communication and Advertising, Advertising Strategy Research, Determining the Advertising Budget, Developing the Creative Strategy, Pretesting the Advertising Campaign, Evaluating the Advertising Campaign, How to Make Winning Presentations, Index.
Preface, Introduction: What Advertising Is All About, Marketing and the Marketing Plan and Advertising, Communication and Advertising, Advertising Strategy Research, Determining the Advertising Budget, Developing the Creative Strategy, Pretesting the Advertising Campaign, Evaluating the Advertising Campaign, How to Make Winning Presentations, Index.